AgriTech4Egypt innovation challenge: That’s a wrap - Zaccari, Claudia; Loiseau, Camille (2025)
On 17 December 2024, the AgriTech4Egypt Innovation Challenge wrapped up months of hard work through its final Demo Day, aimed at celebrating the achievements of 15 Agri-Tech innovation teams who successfully completed an intensive acceleration program, chosen from 900 applicants across 48 countries. Read the full article.